Evidence of artificial selection: are orchids in cultivation an effective ex situ conservation strategy? - Tremblay, Raymond L.; Alicea-Roman, Paola A.; Anaya-Reyes, Abimelys; Duclerc-Rodas, Sean; Medina-Tirado, Ivanellys (Lankesteriana: International Journal on Orchidology, 2022)
Artificial selection is the process by which humans change morphological and genetic characteristics of species through selection of “favored” characters. Although the gray literature suggests the process is occurring in orchids held in ex situ collections, there is limited evidence of this in the scientific literature. There is a perspective among growers that species (not hybrids) held in ex situ collections are potential sources of material for use in in situ re-establishment, however, this assumes that there has not been any artificial selection for morphological characters, or functional traits while grown and propagated ex situ. Here we evaluate if plants grown in ex situ collections show changes in morphological characters across time and if the range of character size is within the range from in situ populations. We evaluated plants from the American Orchid Society database from nine genera and 54 species. We noted that 35% of characters evaluated had evidence of significant change across time. Moreover, for most species in ex situ the evaluated characters were frequently (95%) outside the range of plants of natural populations based on species descriptions. If variation in size of ex situ collections as compared to in situ plants is genetically based, it is possible that these would be functionally maladaptive if re-introduced to their natural environment. Protocols for ex situ conservation programs need to focus on the morphological, biochemical, and ecological interactions and genetic diversity that would render the re-introduction of ex situ to their natural environment to maximize the likelihood of effective re-establishment. Consequently, species which are awarded recognition at orchid shows may potentially be inappropriate for plants within an in situ reintroduction conservation program.